2018
DOI: 10.13057/biodiv/d190612
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Development of selected PGPR consortium to control Ralstonia syzygii subsp. indonesiensis and promote the growth of tomatoYanti Y, Warnita, Reflin. 2018. Short Communication: Development of selected PGPR consortium to control Ralstoni

Abstract: Yanti Y, Warnita, Reflin. 2018. Short Communication: Development of selected PGPR consortium to control Ralstonia syzygii subsp. indonesiensis and promote the growth of tomato. Biodiversitas 19: xxxx. A microbial consortium is a group of different species of microorganisms and acts as a community. Combinations of biocontrol strains are expected to have a better result to suppress multiple plant diseases. Our previous research had selected four plant growth promoting rhizobacteria (PGPR) strains from chili (B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…SWRIIA02 in seeds gave the best results on chili growth and yield, so it can be stated that the two types of rhizobacteria are mutually compatible. In line with the results of this study, it was reported that the use of a mixture of two or more types of rhizobacteria significantly increased the yield of maize [37] dan tomato [38].…”
Section: Discussionsupporting
confidence: 90%
“…SWRIIA02 in seeds gave the best results on chili growth and yield, so it can be stated that the two types of rhizobacteria are mutually compatible. In line with the results of this study, it was reported that the use of a mixture of two or more types of rhizobacteria significantly increased the yield of maize [37] dan tomato [38].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, 20 ml of of R. syzygii subsp. Indonesiensis suspension with a density of 107 cells/ml was sprinkled on the roots of the chili plants that had been injured [10].…”
Section: Pathogenicity Testmentioning
confidence: 99%
“…The planting medium used was a mixture of soil and manure (2:1 v/v). The planting medium is put in a plastic bag and then sterilized in a boiler for 1 hour at 100 0 C. The planting medium was put 5 g into a pottray for seeding and 10 kg into a polybag for planting [10].…”
Section: Preparation Of Planting Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the ability of PGPR to increase the activity of defense enzymes in plants, including cucumber roots treated with Pseudomonas corrugata 13 or Pseudomonas aureofaciens 63-28 can increase phenylalanine ammonia-lyase (PAL) activities, peroxidase (PPO) and polyphenol oxidase (PO) activity (Chen et al 2000). Turmeric plants introduced with Bacillus amyloliquefaciens BaTNAU5 and Pseudomonas fluorescens strain Pf3TNAU triggered an increase defense enzymes peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL), β- were 3 root bacteria and 4 endophytic bacteria which were able to suppress whitefly populations and tomato wilt disease (Yanti 2018 andHamid 2020). This study aims to determine the activity of the PPO, PO and PAL defense enzymes with selected PGPR isolates.…”
Section: Introductionmentioning
confidence: 99%